2D Electrical Resistivity Tomography interpretation ambiguity - example of field studies supported with analogue and numerical modelling - Bania, Grzegorz; Ćwiklik, Michał (Geology, Geophysics and Environment, 2013)
Single Electrical Resistivity Tomography (ERT) survey was carried out in the Manor and Park Complex in Nowa Huta (Krakow Branice, Poland). It was applied at a small distance and parallel to the longer wall of a monumental building containing an empty 3 m deep basement. Analogue modelling was performed in order to recreate the field study at the proper scale. The laboratory set-up consisted of a water tank where electrodes were mounted to the particular plate, which rested on water surface. The basement model was made out of a non-conducting material. The default and robust inversions were tested and these variants were also considered with the use of numerical modelling. Laboratory experiments have confirmed that zones visible in the interpreted field section are caused by the influence of the building cellar located next to the survey line. Zones of this kind are additionally disturbed by the local geological structure. The experiment has pointed out, among others, that as the distance between the survey line and the underground body increases, the inversion results are still burdened by an object influence. Thus, similar situations can be verified with the use of analogue modelling presented in this paper or 3D numerical one.